Mind as motion : explorations in the dynamics of cognition - Port, Robert F.; Van Gelder, Timothy (MIT Press, 1995)
Mind as Motion is the first comprehensive presentation of the dynamical approach to cognition. It contains a representative sampling of original, current research on topics such as perception, motor control, speech and language, decision making, and development. Included are chapters by pioneers of the approach, as well as others applying the tools of dynamics to a wide range of new problems. Throughout, particular attention is paid to the philosophical foundations of this radical new research program.